Zur Anwendung quantitativer Verfahren bei geomorphologischen Untersuchungen deutschsprachiger Wissenschaftler im Zeitraum 1970-1987: Ein kurzer Literaturbericht - Siegburg, Werner (ERDKUNDE, 1989)
For the purpose of studying the application of quantitative methods by German-speaking geomorphologists, a sample of 1,062 publications dated between 1970 and 1987 was taken and evaluated. The most significant results and conclusions are as follows: 1) Quantitative methods were applied in 10.04% of the geomorphological studies. This figure has certainly risen in comparison to earlier years. Such procedures are, however, much more common in certain non-German-speaking countries and in other geographical fields and subjects related to geography. 2) In 60.6% of all the statistical analyses simple univariate and bivariate methods were used, whereas multivariate procedures were applied in a mere 0.6-7 % of the analyses, although geomorphological processes and forms are usually multicausal in origin and must be considered with in the context of a complex system. Three examples taken from periglacial and slope morphology make it obvious that the application of quantitative procedures can lead to results which are beyond the scope of traditional methods. The relatively uncommon use of multiple statistics may partly be due to the present level of research, and partly to the fact that multivariate analyses, when involving a large number of data and variables, are only feasible with the aid of electronic data processing. On the other hand, however, a complex data analysis is aided by the availability of comprehensive software (i.e. statistical packages such as SPSS or SAS). 3) The proportion of quantitative studies varies considerably in the differing geomorphological fields. In general this depends more on the acceptance of statistical methods than on their applicability. 4) The application of quantitative statistics also varied with regard to the relief features studies. The corresponding percentages range between 0.5% and 34.1% (table4). The traditional employment of semi-quantitative methods in the analysis of certain features, or the fact that some kinds of variables are easy to quantify, has obviously resulted in a greater popularity of statistical procedures, where as in other cases the recording of data is considered too time consuming and involves the employment of a large number of technical instruments.